The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/jpln.201200414
|View full text |Cite
|
Sign up to set email alerts
|

Potassium and stress alleviation: Physiological functions and management of cotton

Abstract: Potassium (K) plays a major role in the basic functions of plant growth and development. In addition, K is also involved in numerous physiological functions related to plant health and resistance to biotic and abiotic stress. However, K deficiency occurs widely resulting in poor growth, lost yield, and reduced fiber quality. This review describes the physiological functions of K and its role in stress relief and also provides some agronomic aspects of K requirements, diagnosis of soil and plant K status, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(88 citation statements)
references
References 145 publications
2
70
0
7
Order By: Relevance
“…Increasing the level of soil exchangeable K by fertiliser application would render more K available to plants for the needs of physiological functions (e.g. photosynthesis and turgor maintenance) and for better root growth under soil-water deficit (Grzebisz et al 2013;Oosterhuis et al 2013). Consistently in the present study, the positive response of wheat growth and grain yield to soil K supply was observed at the drought-affected site but not at the non-stressed sites.…”
Section: Soil K Supply and Droughtsupporting
confidence: 89%
See 1 more Smart Citation
“…Increasing the level of soil exchangeable K by fertiliser application would render more K available to plants for the needs of physiological functions (e.g. photosynthesis and turgor maintenance) and for better root growth under soil-water deficit (Grzebisz et al 2013;Oosterhuis et al 2013). Consistently in the present study, the positive response of wheat growth and grain yield to soil K supply was observed at the drought-affected site but not at the non-stressed sites.…”
Section: Soil K Supply and Droughtsupporting
confidence: 89%
“…Fertiliser K supply at Dowerin increased K concentration and content in shoots, total dry matter and grain yield. During soil drying period, the decrease in soil water potential would likely impair K movement to the root surface and reduce plant K uptake (Marschner 1995;Römheld and Kirkby 2010;Oosterhuis et al 2013). On the other hand, soil K deficiency reduces root growth to a greater extent than shoot growth in wheat and barley (Ma et al 2011(Ma et al , 2013, likely attributable to the critical role of K in supplying sucrose from leaves to roots to meet the energy requirements for root growth and ion uptake (Cakmak et al 1994;Marschner et al 1996).…”
Section: Soil K Supply and Droughtmentioning
confidence: 99%
“…A previous study showed that fertilization with K was causing a decreased allocation to roots, which enables increased growth in height and leaf number [38]. Moreover, the viewpoint that an optimal potassium nutrition status can reduce the effects of abiotic stresses, such as drought, heat, high light intensity, or salinity has been well established [14,39,40]. The characteristic of our study site is coastal sandy saline-alkali soil; thus, K fertilizer is essential in Yellow Sea Forest Park.…”
Section: Discussionmentioning
confidence: 89%
“…Potassium due to its impact on many physiological processes plays an important role in water use by crop plants (Grzebisz et al, 2013 andOosterhuis et al, 2013). A main function of K is unloading sugars from chloroplasts to phloem cells, and from phloem cells into storage cells such as grains, (Salisbury and Ross, 1978).…”
Section: Yieldmentioning
confidence: 99%